Spinal dysraphism: MRI evaluation - ., Ramacharya; Desai, Kiran S. (International Journal of Research in Medical Sciences, 2017)
Background: Spinal dysraphism refers to the entire range of spinal column and neuraxis anomalies. The objective was to evaluate the role of magnetic resonance imaging (MRI) in characterizing the congenital and developmental disorders of spine. Methods: Fifty (50) patients with clinically suspected spinal dysraphism were included in the study. All the patients were made to undergo MRI spine using 1.5 Tesla MRI, manufactured by GE, SIGNA HDX MACHINE. The findings of MRI spine were assessed and analyzed. Results: Out of 50 patients included in the study; 24 were male (48%) and remaining 26 were female (52%). Congenital spinal lesions were more prevalent in the age group 0-20 years (70%). Lesions without subcutaneous masses (62%) were more common than the lesions with subcutaneous masses (38%). The commonest location for the congenital spinal lesions was lumbar region (54%). Congenital spinal lesions without spinal curvature abnormalities (58%) were more common than the lesions with spinal curvature abnormalities (42%). Vertebral anomalies (78%) were the commonest spinal anomalies in patients with congenital spinal lesions; spina bifida was the commonest (46%). Diastematomyelia was more prevalent in the age group 0-10 years (41.66%) and in female population (58.33%). Conclusion: Thus we conclude that Spinal dysraphism were common in young females, with commonest anomaly being vertebral anomaly (Spina bifida), commonest location is lumbar region, Diastematomyelia common in young aged female. Magnetic resonance imaging is an accurate, noninvasive, safe and advanced modality for evaluation of the congenital spinal disorders and help in better management of these patients with prompt and accurate diagnosis.